Evaluation of deep vein thrombosis prophylaxis use in a Northwest Ethiopian medical ward: an observational follow-up study - Dagnew, Samuel Berihun; Moges, Tilaye Arega; Dagnew, Fisseha Nigussie; Assefa, Abraham Nigussie; Anberbr, Sisay Sitotaw; Geremew, Adane Tsegaw; Addis, Getu Tesfaw (Frontiers in Medicine, 2025)
BackgroundDuring hospitalization, a significant number of patients at risk of thromboembolism do not receive prophylaxis, despite established standards and viable procedures for preventing deep vein thrombosis (DVT). This study aimed to assess the appropriateness of vein thrombosis prophylaxis use among patients admitted to the medical ward of Debre Tabor Comprehensive Specialized Hospital (DTCSH) in Northwest Ethiopia.MethodsAn observational follow-up study was conducted in the medical wards of Debre Tabor Comprehensive Specialized Hospital in Northwest Ethiopia to determine whether thromboprophylaxis was appropriately used, based on the Padua risk assessment tool. To identify factors associated with the occurrence of inappropriate thromboprophylaxis use, a binary logistic regression model was used. Statistical significance was considered when the p-value was <0.05, with a 95% confidence interval.ResultsAmong the 365 patients in the study, 21.37% received inappropriate thromboprophylaxis, while 78.63% received it correctly. Patients admitted to the ICU [AOR = 4.276, 95% CI: 1.878–16.134; p = 0.000], those who stayed for more than 6 days [AOR =6.192, 95% CI: 2.085–14.391; p = 0.000], and general practitioners [AOR = 1.816, 95% CI: 1.007–3.207; p = 0.048] were more likely to receive inappropriate thrombophylaxis.ConclusionThe appropriateness of DVT prophylaxis use was suboptimal, especially among the patients treated by general practitioners, those hospitalized in the intensive care unit, and those who stayed for more than a few days in the ward. Using an integrated risk stratification checklist is an effective way to promote the more rational use of DVT prophylaxis.